Maximum power point tracking for a small scale wind turbine with permanent magnet synchronous generator - Torres, Jan Vincent T. (2011)
The absence of fuel in renewable energy (RE) power generation can be well exploited by extracting the maximum energy available at any time from the RE source. Energy yield improvement of such on-site small WTs with PMSG systems may only be realized through active control of its electrical parameters, such as voltage, frequency, and current. In this project, a PMSG WT battery charger was developed. It was equipped with a maximum power point tracking (MPPT) algorithm that does not require a wind speed sensor. This algorithm ensures optimum energy extraction from the available power of the turbine. The MPPT algorithm used was the hill-climbing search algorithm (HCSA) with initial approximation. An adaptive initial approximation algorithm for the HCSA where initial estimates of the electrical parameters at the MPP are moved closer to the actual MPP during each traversal was also developed. The algorithm was implemented using the Zilog microcontroller Z8 Encore! Z8F2480, and was used to control a 500W multimode synchronous buck-boost converter. The project was tested using a 500W turbine with part number YWL-500 of A-Wing International, and data suggest that the developed converter's energy extraction algorithm is at par with the A-Wing controller YWS-500.
Undergraduate student project (B.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Wind turbines; DC-to-DC converters -- Design; Buck-boost converter; Maximum power point tracking (MPPT).